Techno-Stress: Damage Caused by New Emerging Risks - Rubén Rodríguez Elizalde (Laws, 2021)
The world moves and advances very quickly. Production systems and jobs evolve with the world. Occupational risks change as jobs change: The occupational risks of jobs we found two hundred years ago are different from the risks inherent to today’s jobs. The influence of technology is evident in many of today’s companies and, as a consequence, in the work that takes place in them. The recent COVID-19 pandemic, which has so upset the world, has made possible the acceleration in the massive use of certain communication tools that has been linked to the home confinement of a significant part of the population. Lots of workers and companies have been forced to telecommute. In a lot of countries, legislation and regulations were not prepared for these new ways of working: the laws have had to adapt to this new operation. In this area techno-stress has emerged, a new variety of stress derived from the use of new technologies at work, with the consequent negative psychosocial effects for the worker and the people around him, which can, at the same time, be the prelude to many others pathological processes of various nature.